2014
DOI: 10.1016/j.biomaterials.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A phenotypic culture system for the molecular analysis of CNS myelination in the spinal cord

Abstract: Studies of central nervous system myelination lack defined in vitro models which would effectively dissect molecular mechanisms of myelination that contain cells of the correct phenotype. Here we describe a co-culture of purified motoneurons and oligodendrocyte progenitor cells, isolated from rat embryonic spinal cord using a combination of immunopanning techniques. This model illustrates differentiation of oligodendrocyte progenitors into fully functional mature oligodendrocytes that myelinate axons. It also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…15 However, these strategies are only partial solutions since it will be more difficult with increasing number of organs, and obviously, the development of a universal as well as chemically well-defined media that can support growth and differentiation of all cell types would be a more complete solution. Hickman et al demonstrated using a serum-free medium for supporting coculture of muscle cells derived from human stem cells and sensory neurons, 127 and coculture of motoneurons and oligodendrocyte, 128 as well as in their 4-organ systems, 25 which show great promise for a coculture systems with a larger number of organs. 25 Second, development of biomaterials that meet specifications of different cell types is also needed to further improve current BOC models.…”
Section: ■ Recent Advances In Multiorgan Modelsmentioning
confidence: 99%
“…15 However, these strategies are only partial solutions since it will be more difficult with increasing number of organs, and obviously, the development of a universal as well as chemically well-defined media that can support growth and differentiation of all cell types would be a more complete solution. Hickman et al demonstrated using a serum-free medium for supporting coculture of muscle cells derived from human stem cells and sensory neurons, 127 and coculture of motoneurons and oligodendrocyte, 128 as well as in their 4-organ systems, 25 which show great promise for a coculture systems with a larger number of organs. 25 Second, development of biomaterials that meet specifications of different cell types is also needed to further improve current BOC models.…”
Section: ■ Recent Advances In Multiorgan Modelsmentioning
confidence: 99%
“…[166] The formula were further adapted to support reliable long-term culture of skeletal myotubes, [167] cardiomyocytes, [125] and motoneurons, [22,168] as well as dual culture of motoneurons with sensory neurons to build the stretch reflex arc, [169171] or with oligodendrocyte progenitor cells to model myelination. [172] This laid a foundation for introducing serum-free cell culture media into the multi-organ systems. Recently, Oleaga et al demonstrated in a four-organ MOM, in which serum-free culture medium maintained hepatic function, cardiac and neuronal electrical activity, and cardiac and skeletal muscle contraction capacity.…”
Section: Challengesmentioning
confidence: 99%
“…Models for both CNS and PNS myelination have been established to promote neuron-neuron and neuron-muscle communication and to study diseases involving demyelination and injury repair. 26,81,82 A higher degree of neuronal communication is the reflex arc circuit (CNS-PNS link). The sensory and the effector portions have been successfully reproduced in vitro under controlled conditions.…”
Section: Cns and Peripheral Nervous System (Pns)-on-a-chipmentioning
confidence: 99%
“…In 1995, the Hickman group implemented such an approach in experiments with hippocampal neurons. 21 Further research has led to the successful adoption of defined and serum-free medium formulations for (i) single cultures of skeletal myotubes, 22 cardiomyocytes, 23 and motoneurons 20,24 ; (ii) dual cultures of motoneurons with skeletal muscle (to form neuromuscular junctions), 17 sensory neurons (to recreate the stretch reflex arc), 16,25 or oligodendrocyte progenitor cells (to model myelination) 26 ; and (iii) multi-organ cultures with four different organ types. 7…”
Section: Controlled Culture Environmentmentioning
confidence: 99%